Automatic sport facilities management system (UMPASFMS) - Hooi Fong, Tan (2012)
UMP-Automatic Sports Facilities Management System(UMPASFMS) was proposed to help UMP Sports Complex manage its facilities and ease the process of borrowing the sports facilities.This system will update the list of facilities available in the database every time booking process is completed.It also provides a preview of booking status to its user.In addition, it helps admin to manage the facilities’information efficiently.Admin can search for particular facilities and easily view its information,as well as keep track of the available facilities.UMPASFMS was developed using Microsoft Visual Studio 2010 as the web development tool,Microsoft SQL Server R2 Express Edition as the database software,Internet Information System (IIS) as the web server,ASP.Net as presentation layer,and C# language as the web scripting language.UMPASFMS follows the Rapid Application Development (RAD) methodology in order to keep the schedule of this system more systematic and finish by the appointed time.